Correlation of Magnetic Resonance Spectroscopy Changes in Hippocampal and Perihippocampal Regions and Neuro-Psychologic Evaluation with Various Clinical Factors Following Whole Brain Radiotherapy in Brain Metastasis - Krishna AS, Uday; Naveen, Thimmaiah; Phesao, Vezokhoto; Tanvir, Pasha; Lokesh, V (Reports of Radiotherapy and Oncology, 2019)
Objectives: To study the correlation of magnetic resonance spectroscopy (MRS) changes in hippocampal and perihippocampal regions and neuro-psychologic evaluation with various clinical factors following whole brain radiotherapy in brain metastasis. Methods: A total of 33 patients with newly diagnosed brain metastasis, referred to our Department of Radiation Oncology were recruited after a prior informed written consent. All patients underwent baseline clinical/neurological evaluation, detailed MMSE examination, gadolinium enhanced MRI along with MRS (for ratio of Choline: NAA = CNI) from the bilateral hippocampal and perihippocampal areas. All patients then underwent WBRT by two opposing lateral portals on a linear accelerator to a dose of 30 gray in 10 fractions delivered over 2 weeks. Serial evaluations along with MRS and MMSE score were done at 1st, 3rd and 6 months after WBRT. The trends of CNI and MMSE scores at last follow-up were correlated with various clinical factors. Results: Our cohort had 33 patients, predominantly women (M:F, 12:21) with a median age of 47 years, median KPS (Karnofsky performance status) of 80, mean RPA (recursive partitioning analysis) class 2, primary histology (lung, breast, GI, Gy, GU, MUO (metastasis of unknown origin): 10, 11, 2, 4, 4, 2). Median survival of the cohort was 4 months. At the end of 14 months of follow-up 30% of the patients were alive with a mean KPS of 70. Trend in the CNI values with time showed that, KPS (P = 0.079), RPA class (P = 0.079), primary diagnosis site (P = 0.049), number of brain metastasis (P = 0.045) showed statistical significance in terms of change in mean value of CNI value at last follow-up. Site of primary (lung/breast vs. others, P = 0.02) and number of metastasis (solitary/oligo vs. multiple, P = 0.02) showed significant correlation with decline in CNI. The KPS at presentation (< 70 or > 70, P = 0.04); RPA class (class II or higher, P = 0.04); Site of primary (lung/breast vs. others, P = 0.01), presence of extracranial disease (yes or no, P = 0.045), number of metastasis (solitary/oligo vs. multiple, P = 0.06), Size of the largest metastatic lesion (< or > 4 cm, P = 0.02) showed significant correlation with decline in MMSE at last follow-up. Conclusions: Cognitive functioning after WBRT is influenced by a number of factors; patient related, systemic disease burden and local tumor load. Local disease control has significant impact on preservation of neurocognition. The trend in the CNI index and MMSE scores at last follow-up correlated with various factors and can be used as a guide to aid in patient selection for hippocampus- avoidance WBRT.